Microplastics in the Environment and Human Health: Current State of Knowledge and Future Research Directions - Majda , Antoni; Sławatyniec, Olga; Sobieraj, Wiktoria; Pająk, Julia; Kamosińska, Anna; Łuniewska , Wiktoria; Modrzyk , Marta; Kucharski, Kacper; Kowal, Adam (Journal of Education, Health and Sport, 2026)
Microplastics (MPs) are plastic particles smaller than 5 mm in size. They have become one of the most ubiquitous environmental contaminants worldwide. Their presence has been documented in all major environmental reservoirs, including oceans, rivers, soils, and the atmosphere, and in recent years they have also been detected directly in human tissues and bodily fluids. This review paper presents the current state of knowledge regarding the sources, distribution, and environmental impacts of microplastics, pathways of human exposure, and the mechanisms underlying their potential effects on health. Particular attention is devoted to evidence concerning the presence of microplastics in the respiratory, gastrointestinal, cardiovascular, and urogenital systems, as well as their influence on the gut microbiome. Existing clinical evidence is also discussed, including the landmark study published in The New England Journal of Medicine in 2024, which demonstrated an association between the presence of microplastics in atherosclerotic plaques and an increased risk of cardiovascular events. Future research priorities and strategies for reducing exposure at both individual and systemic levels are also presented.